Infrared assisted digestion used as a simple green sample preparation method for nutrient analysis of animal feed by microwave induced plasma atomic emission spectrometry - Cora Jofre, Florencia; Larregui, Daiana Natali; Murcia, Vanina Nerea; Pacheco, Pablo; Savio, Marianela (Elsevier, 2022)
Based on green analytical chemistry principles it is important to evolve procedures that convert solid samples into solutions without using excessive reagent quantities, energy, temperature, and avoiding waste generation. To reach this aim, a simple infrared assisted digestion (IRAD) method for animal feed analysis was proposed. Infrared radiation (IR) with 2 mL of HNO3 and 2 mL of H2O2 were assessed, presenting low dissolved organic carbon (DOC) and residual acidity (RA) in the final digest, being fully compatible with microwave induced plasma atomic emission spectrometry (MIP OES). Calcium, Cd, Cu, Fe, K, Mg, Na, P, Sr and Zn were determined in reference materials and in animal feeds. Limits of quantification were between 2.52 and 284 mg kg−1 for Ca and P respectively. Recovery values ranged 80–120%, with relative standard deviations (RSD%) under 8%. The friendliness offered by the IRAD MIP OES method was evaluated by two green indexes. Concentrations in feedstuffs were compared with National Research Council (NRC) recommendations.